Functional conservation and divergence of Miscanthus lutarioriparius GT43 gene family in xylan biosynthesis. Issue 1 (December 2016) - Wang, Xiaoyu; Tang, Qi; Zhao, Xun; Jia, Chunlin; Yang, Xuanwen; He, Guo; Wu, Aimin; Kong, Yingzhen; Hu, Ruibo; Zhou, Gongke
Abstract Background Xylan is the most abundant un-cellulosic polysaccharides of plant cell walls. Much progress in xylan biosynthesis has been gained in the model plant speciesArabidopsis . Two homologous pairsIrregular Xylem 9 (IRX9)/9L andIRX14/14L from glycosyltransferase (GT) family 43 have been proved to play crucial roles in xylan backbone biosynthesis. However, xylan biosynthesis in grass such asMiscanthus remains poorly understood. Results We characterized seven GT43 members inM. lutarioriparius, a promising bioenergy crop. Quantitative real-time RT-PCR (qRT-PCR) analysis revealed that the expression ofMlGT43 genes was ubiquitously detected in the tissues examined. In-situ hybridization demonstrated thatMlGT43A-B andMlGT43F-G were specifically expressed in sclerenchyma, whileMlGT43C-E were expressed in both sclerenchyma and parenchyma. All seven MlGT43 proteins were localized to Golgi apparatus. Overexpression ofMlGT43A-E but notMlGT43F andMlGT43G inArabidopsis irx9 fully or partially rescued the mutant defects, including morphological changes, collapsed xylem and increased xylan contents, whereas overexpression ofMlGT43F andMlGT43G but notMlGT43A-E complemented the defects ofirx14, indicating thatMlGT43A-E are functional orthologues ofIRX9, whileMlGT43F andMlGT43G are functional orthologues ofIRX14 . However, overexpression of all sevenMlGT43 genes could not rescue the mucilage defects ofirx14 seeds. Furthermore, transient transactivation analyses ofMlGT43A-E reporters demonstrated thatMlGT43A andMlGT43B but notMlGT43C-E were differentially activated byMlSND1, MlMYB46 orMlVND7 . Conclusion The results demonstrated that all seven MlGT43s are functionally conserved in xylan biosynthesis during secondary cell wall formation but diversify in seed coat mucilage xylan biosynthesis. The results obtained provide deeper insight into xylan biosynthesis in grass, which lay the foundation for genetic modification of grass cell wall components and structure to better suit for next-generation biofuel production.